1998
DOI: 10.1021/om970831m
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Degradation of the Rhenium Silyl Ester Cp(NO)(PPh3)ReCO2SiMe2Ph to the Bimetallic μ-η1(C(Re)):η1(O,O‘(Re)) Carbon Dioxide Complex Cp(NO)(PPh3)ReCO2Re(NO)(CO)(PPh3)OSiMe2Ph

Abstract: The silyl esters Cp(PPh3)(NO)ReCO2SiR3 (2) are produced from treatment of Cp(PPh3)(NO)ReCOBF4 with the silanolates R3SiONa (R3Si = PhMe2Si, Et3Si) in CH2Cl2 (0 °C) or of Cp(PPh3)(NO)ReCO2K with R3SiCl in THF. Upon handling, 2 degraded to the bimetallocarboxylates Cp(PPh3)(NO)ReCO2Re(CO)(NO)(PPh3)(OSiR3) (3), one of which (SiR3 = SiMe2Ph) was characterized by X-ray crystallography as a μ-η1(C(Re1)):η2(O,O‘(Re2)) bimetallocarboxylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Rearrangement of 8 to 2 followed by silanolysis of the Re-η 1 -Cp yields the observed products. Indeed, treatment of Cp(NO)(PPh 3 )ReCO + BF 4 - with 1 equiv of 1 K + followed by addition of silanol R 3 SiOH conveniently gave 5 (even though 2 had not been detected) . In the present study, we found that treating the isolated and fully characterized 2 with Et 3 SiOH delivered 5a (eq 5).…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…Rearrangement of 8 to 2 followed by silanolysis of the Re-η 1 -Cp yields the observed products. Indeed, treatment of Cp(NO)(PPh 3 )ReCO + BF 4 - with 1 equiv of 1 K + followed by addition of silanol R 3 SiOH conveniently gave 5 (even though 2 had not been detected) . In the present study, we found that treating the isolated and fully characterized 2 with Et 3 SiOH delivered 5a (eq 5).…”
Section: Resultssupporting
confidence: 46%
“…We rule out either of the 1482 and 1436 cm -1 bands (weak and medium relative intensities, respectively) as candidates for the ν OCO(asym) assignment, since absorptions with identical energies and relative band shapes are found for Cp(PPh 3 )(NO)ReH and Cp(PPh 3 )(NO)ReCH 3 . Previously, we had assigned the medium to strong intensity ν OCO(sym) and ν OCO(asym) bands for 5a (in THF) at 1290 and 1249 cm -1 and those for 5b at 1287 and 1248 cm -1 ; both molecules likewise exist as 1:1 to 1:2 diastereomeric mixtures . It therefore seems plausible that the ν OCO bands for 2 fall within the 1300−1200 cm -1 region.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…There are two other structures of dimethylphenylsiloxo metal derivatives in the CSD, apart from [{Me 2 Al(OSi-Me 2 Ph)} 2 ], viz. tetrakis[( 6 -benzene)(" 3 -dimethylphenylsiloxo)potassium] (Fuentes et al, 1991) and a rhenium complex (Tetrick et al, 1998). Of these three complexes, only [{Me 2 Al(OSiMe 2 Ph)} 2 ] shows some similarities with (I).…”
Section: Commentmentioning
confidence: 99%